Can we overcome the challenges of sutures in lamellar keratoplasty? - Panda, Anita (Medknow Publications, 2011)
Lamellar keratoplasty (LK) is a technique which can be followed for both tectonic and optical purposes. We describe a technique of sutureless anterior LK by fixing the donor lenticule to the recipient bed using fibrin glue. LK was performed in an eye with corneal opacity using the manual dissection method. The donor lenticule was cut with a microkeratome after fixing the corneoscleral rim in an artificial anterior chamber. The size of the donor lenticule was 8.5 mm and fixed to the recipient bed with fibrin glue. The surgical time was reduced significantly with this technique. There was an uneventful postoperative period during the follow-up of 12 months. Best corrected visual acuity improved from hand movement to 20/60. Thus, the use of fibrin glue for fixing the anterior lamellar lenticule is a viable option for both optical and anatomical purposes.